HEALTH AND LIFE QUALITY AT WORK: THE CASE OF TEACHERS AND STAFF ADMINISTRATIVE AN INSTITUTION OF PRIVATE TEACHING IN THE CITY OF PONTA GROSSA (Fiep Bulletin - online, 2017)
This study aimed to assessing the quality of working life of employees of a private educational institution in the city ofPonta Grossa/PR. a comparison of the results of the two working classes surveyed was held at the institution, to be identifiedwhich class is considered to better health and quality of working life. The approach is characterized as applied, quantitative andexploratory. Regarding the technical and methodological procedures used in this study, the population is formed by teacherstotaling 22 teachers and administrative staff totaling 14 individuals. The procedure adopted for data collection was developed byanalyzing instrument application called by Questionnaire QWLQ-78, which aims to assess the health and quality of working lifeunder the personal point of view, health, psychological and professional . has as main result of the study the level of health andquality of working life from his point of view and knowledge of the procedures and actions developed by the worker in hisprofession. The results show that in the sample of teachers there is a greater disparity in the responses, indicating higher extremevalues and lower, while the sample group of administrative employees, the values assigned to the answers are closer to eachother. Regarding the domain that showed a lower result has the physical domain/health, that despite being within a levelconsidered neutral, deserves attention by the institution, this result was obtained by an employee of the teachers class. Alreadythe highest result was given by the psychological domain, and this result was also obtained by an employee of the class teacher,confirming the disparity in the responses of teachers.